Child protection system involvement in children of incarcerated mothers: A linked data study. (May 2023) - Segal, Leonie; Dawe, Sharon; Nguyen, Ha; Dennison, Susan; Gnanamanickam, Emmanuel S.; Bell, Megan; Spittal, Matthew; Kinner, Stuart; Preen, David B.
Abstract: Background: Women prisoners are a growing portion of the prison population. Health and social outcomes of their children have been studied and found to be poor, but little is known about child protection outcomes. Objectives: Ascertain child protection system contact of children exposed to maternal incarceration. Participants and setting: All children born between 1985 and 2011 exposed to the incarceration of their mothers in a Western Australian correctional facility and a matched comparison group. Methods: A matched cohort study using linked administrative data on 2637 mothers entering prison between 1985 and 2015 and their 6680 children. We estimated hazard ratios (HRs) and incidence rate ratios (IRRs) of child protection service (CPS) contact post maternal incarceration (four concern levels), comparing rates for children exposed to maternal incarceration with a matched non-exposed group, adjusting for maternal and child factors. Findings: Exposure to maternal incarceration increased risk of CPS contact. Unadjusted HRs exposed vs unexposed children were 7.06 (95%CI = 6.49–7.69) for substantiated child maltreatment and 12.89 (95%CI = 11.42–14.55) for out-of-home care (OOHC). Unadjusted IRRs were 6.04 (95%CI = 5.57–6.55) for number of substantiations and 12.47 (95%CI = 10.65–14.59) for number of removals to OOHC. HRs and IRRs were only slightly attenuated in adjusted models. Conclusions: Maternal incarceration is a warning flag for a child at high risk of serious child protection concerns. Family-friendly rehabilitative women's prisons, incorporating support for more nurturing mother-child relationships could provide a placed-based public health opportunity for disrupting distressing life trajectories and intergenerational pathways of disadvantage of these vulnerable children and their mothers. This population should be a priority for trauma-informed family support services. Highlights: Women prisoners are a growing portion of the prison population. Children of incarcerated mothers have much greater risk of child protection concerns. Services must do more to ensure these children and families receive needed support. Family friendly prisons are an opportunity to support enhanced parenting capacity.